THE MODELING OF RAINFALL-RUNOFF OF DAS TOJO CENTRAL SULAWESI USING HEC-HMS SOFTWARE - Teguh Hilmansyah; Aswar Amiruddin; Moh Amin; Sukardi Nurdin (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2023)
In the hydrological cycle, the rain falling on the ground surface in a watershed (DAS) then undergoes a process of evaporation, infiltration, and surface runoff. This conversion of rain into runoff surface can be used as a basis for calculating the discharge of the design flood. Analyzing flood design is one of the calculations in water resource planning. River flow discharge is an indicator of the output of a watershed system, especially in the process of converting rainfall into a surface flow. Flood discharge in a watershed is generally expressed as a hydrograph. One method that can be used to analyze the conversion of rain into flow is the HEC-HMS software. The purpose of this research is to determine the design of flood discharge and flow hydrograph of Tojo River using HEC-HMS software. In this article, the HEC-HMS model components used to analyze hydrographs are SCS CN for the runoff volume model and SCS UH for the direct runoff model. From the results of modeling using HEC-HMS, the peak flow discharge of the Tojo watershed in Central Sulawesi are 133.8 m3/s for a 2-year design flood, 239.8 m3/s for a 5-year design flood, 329.5 m3/s for 10-year design flood, 442.5 m3/s for 20-year design flood, 589.8 m3/s for 50-year design flood and 727.1 m3/s for 100-year design flood. Furthermore, the results of this study can be used for flood control planning and other water resource planning.Keywords: Flood Design, Das Tojo, HEC-HMS